2022
DOI: 10.1344/der.2022.41.114-123
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Screen Time and Mobile Dependency on Cognition, Socialization and Behaviour Among Early Childhood Students During the Covid Pandemic- Perception of the Parents

Abstract: Digital technology systems are adopted rapidly throughout the globe for the virtual learning process especially with the outbreak of the Covid-19 pandemic. Digital screen-based gadgets are integrated to provide a seamless interactive medium of learning even before the initiation of formal education. Studies on the technology use of younger children are critical as uncontrolled gadget use affects their developmental stages yet these studies are still in the infancy stage. This study analyses the psychoeducation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In 2021, the number of studies significantly increased to n=9 [19]- [27]. The number of studies remained consistent in 2022 with n=9 [28]- [36], and in 2023 with n=9 studies [37]- [45] respectively. The increase in the number of studies from 2019 to 2023 indicates that research on children's screen time continued to be a priority.…”
Section: Distribution Of Past Studiesmentioning
confidence: 70%
See 2 more Smart Citations
“…In 2021, the number of studies significantly increased to n=9 [19]- [27]. The number of studies remained consistent in 2022 with n=9 [28]- [36], and in 2023 with n=9 studies [37]- [45] respectively. The increase in the number of studies from 2019 to 2023 indicates that research on children's screen time continued to be a priority.…”
Section: Distribution Of Past Studiesmentioning
confidence: 70%
“…The United States has the highest number of studies with n=7 [18], [20], [33], [38], [40], [42], [43]. India follows this with n=5 studies [15], [17], [29], [36], [41]. There are n=3 studies found in Pakistan [24], [26], [28] suggesting a growing awareness of the importance of understanding children's screen time in the country.…”
Section: Distribution Of Past Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Such digital platforms can aid language production, improve comprehension, and letter-object recognition in an entertaining manner. The use of digital gadgets should be planned timely [ 1 ] by the parents/caretakers to ensure that the needs of developing children are met, and they are not involved with these gadgets throughout the day. Physical activity and the feeling of natural surroundings and spending time with the family and social interaction [ 152 ] are also very important and should not be neglected for a healthy daily routine [ 153 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to violent or aggressive content on screens may contribute to the development of aggressive behaviour in young children (Djalalinia et al, 2020). Several studies conducted in India during COVID lockdown reported that the extended use of digital gadgets influenced young children's mobile dependency, socialisation process, cognition, behaviour patterns and exhibited isolation tendencies and behavioural abnormalities among children (Joseph et. al., 2022); more screen time associate with 25.53% higher risk of demanding extra attention, temper tantrums (21.31%), increased aggressiveness (19.90%), became fussier (18.74%) and clinging (18.27%) (Gunasekaran et al, 2022).…”
Section: Impact On Behaviour and Developmentmentioning
confidence: 99%